Equal opportunities for women and men : European Community acts. (Employment and social affairs, 1999)
Equal treatment for men and women is integral to the European Community's social policy. It is crucial both to its social cohesion in the future. The principle of equal treatment has developed from the isolated provision of equal pay for equal work contained in Article 119 of the Treaty, to a fully fledged programme of equality measures. Since the early 1970s the Commission has been a driving force, whether through its proposals for directives, awareness-raising campaigns or funding initiatives, in putting the need for equality under the spotlight, bringing home its importance to the key players, and working in part-nership with them to mean not only the Member States, but also regional and local athorities, the two sides of industry, company, managers, academia, the media and the citizens of Europe themselves.